Effect Of Aromatic Oil Of Three Plants Of Labiatae Gene On Microorganism By Using In Preservation Of Minced Meat (Journal of Pharmaceutical Negative Results, 2022)
The effect of oil extracts of three plants of Labiatae gene, Mentha longifolia, M. spicata and Ocimum basilicum, by the agar well diffusion method, were studied, the total count of the bacteria responsible for spoilage meat was kept at 4-6˚C for different periods (1, 72,192) hours. The results showed that the oils extract were inhibited all the treatment that were studied and more affected inhibition of the growth of Staphylococcus aureus than the growth of other microbes. The total count of the bacteria responsible for meat spoilage decrease in all treatments extracted oils for all different periods. Statistic analysis results showed high significant variations at the level P≤ 0.01 of all the treatment and control for all reservation periods.